Complement in PNH and other hemolytic anaemias 2 - Luzzatto, Lucio (Henry Stewart Talks, 2017)
Genetically defective regulation (somatic), PNH: complement–mediated hemolysis, Flow-cytometry analysis of PNH red cells, Proteins in the lipid bilayer: GPI-anchors, Mutations in the PIG-A gene, Proteins deficient on PNH blood cells, Mechanism of intravascular hemolysis in PNH, Mechanism of action of CD59